Effect of long chain omega-3 polyunsaturated fatty acids on inflammation and metabolic markers in hypertensive and/or diabetic obese adults: a randomized controlled trial - Ellulu, Mohammed S.; Khaza'ai, Huzwah; Ismail, Patimah; Rahmat, Asmah; Abed, Yehia (Co-Action Publishing, 2016)
Background: Obesity is a degree of excess weight that predisposes people to metabolic syndromes via an inflammatory mechanism. Hypertensive and diabetic people have higher risks of developing systemic inflammation. Long chain omega-3 polyunsaturated fatty acids (LC ω-3 PUFAs) can reduce the cardiovascular events and help against inflammation. Objective: To identify the effects of LC ω-3 PUFAs on reducing the levels of inflammatory markers on hypertensive and/or diabetic obese adults. Materials and methods: Sixty-four patients, who were hypertensive and/or diabetic obese with high levels of inflammatory markers, from primary healthcare centers of Gaza City, Palestine, enrolled in two groups of an open-label, parallel, randomized, controlled trial for 8 weeks. Thirty-three patients were in the control group, and 31 patients were in the experimental group. The experimental group was treated with a daily dose of 300 mg eicosapentaenoic acid and 200 mg of docosahexaenoic acid. Materials and methods: Sixty-four patients, who were hypertensive and/or diabetic obese with high levels of inflammatory markers, from primary healthcare centers of Gaza City, Palestine, enrolled in two groups of an open-label, parallel, randomized, controlled trial for 8 weeks. Thirty-three patients were in the control group, and 31 patients were in the experimental group. The experimental group was treated with a daily dose of 300 mg eicosapentaenoic acid and 200 mg of docosahexaenoic acid. Results: Treatment with LC ω-3 PUFAs significantly reduced the level of high sensitivity C reactive protein (hs-CRP) [14.78±10.7 to 8.49±6.69 mg/L, p<0.001], fasting blood glucose (FBG) [178.13±58.54 to 157.32±59.77 mg/dL, p=0.024], and triglyceride (TG) [209.23±108.3 to 167.0±79.9 mg/dL, p<0.05] after 8 weeks of treatment, whereas no significant changes appeared in interleukin 6 (IL-6) and total cholesterol (TC). In the control group, significant reduction was detected for FBG [187.15±64.8 to 161.91±37.9 mg/dL, p<0.05] and TG [202.91±107.0 to 183.45±95.82 mg/dL, p<0.05], and no changes for hs-CRP, IL-6, or TC. By comparing the experimental group with the changes of control group at the endpoint, LC ω-3 PUFAs did not reach the clinical significance in treating effectiveness for any of the clinical variables. Conclusion: LC ω-3 PUFAs have recommended effects on health; the obtained results can improve the role of LC ω-3 PUFAs as a protective factor on inflammation and metabolic dysregulation. The time allowed or the dose used could be insufficient to achieve full treatment affectivity.